2006
DOI: 10.1111/j.1600-0609.2005.00607.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between expression of CD56/NCAM and severe leukostasis in hyperleukocytic acute myelomonocytic leukaemia

Abstract: The expression of CD56/NCAM, a surface marker used in routine immunophenotyping of AML, may help to predict severe and potentially fatal leukostasis in hyperleukocytic acute myelomonocytic leukaemia. These results emphasize the usefulness of this four-stage clinical grading scale for analysing the factors, which lead to severe leukostasis in hyperleukocytic patients. We extend previous findings that the mechanisms of leukostasis are different depending on the involvement of the monocytic lineage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 32 publications
0
16
0
2
Order By: Relevance
“…In previous studies, a decrease in serum NCAM-1 levels has been observed in some cancers, including pancreatic cancer, colon carcinoma and astrocytoma [28][29][30][31]. Elevated expressions of NCAM-1 have also been observed in various cancers, including acute myeloid leukemia, breast cancer, small cell lung carcinoma, glioma and malignant melanomas [32][33][34][35][36][37][38]. These results suggest that soluble forms of NCAM-1 may be an important biomarker CSF Indices the ratio of CSF-albumin over serum-albumin (CSFalbumin/serum-albumin) Fig.…”
Section: Discussionmentioning
confidence: 96%
“…In previous studies, a decrease in serum NCAM-1 levels has been observed in some cancers, including pancreatic cancer, colon carcinoma and astrocytoma [28][29][30][31]. Elevated expressions of NCAM-1 have also been observed in various cancers, including acute myeloid leukemia, breast cancer, small cell lung carcinoma, glioma and malignant melanomas [32][33][34][35][36][37][38]. These results suggest that soluble forms of NCAM-1 may be an important biomarker CSF Indices the ratio of CSF-albumin over serum-albumin (CSFalbumin/serum-albumin) Fig.…”
Section: Discussionmentioning
confidence: 96%
“…Ground glass opacities sparing the lung bases and the subpleural space are evocative of non-cardiogenic pulmonary edema. Pulmonary leukostasis requires endothelial cell activation and expression of various adhesion molecules by the leukemic blasts, including CD56, irrespective of the absolute leukocyte count [21,22]. In this case, CD56 expression on basophilic blasts might have specifically facilitated the development of leukostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Conventional cytogenetic examination using GTG banding revealed a complex karyotype, with multiple numerical and structural aberrations (14 metaphases with structural anomalies consisting of t(1;4) (p35;q35), del(5)(q31->qter), t(5;20)(p15;p13) and 17 metaphases with numeric anomalies: 11 metaphases with hyperdiploidy (47-50 chromosomes) and 6 metaphases with hypodiploidy. t (9,22) or t(6,9) were not identified. del(5)(q31->qter) was confirmed by interphase fluorescence in situ hybridization (FISH) testing ( Figure 3).…”
Section: Case Reportmentioning
confidence: 99%
“…Die höhere Inzidenz der Embolien bei AML und CML im Vergleich zur CLL kann u.a. dadurch erklärt werden, dass die myeloischen Blasten besonders groß sind und daher aus mechanischem Gründen leichter zu Gefäßverstopfungen führen [12].…”
unclassified
“…Bei dieser AML ist lediglich die absolute Blastenzahl mit der Ausbildung von Leukostase korreliert. Weitere Adhäsionsmoleküle werden derzeit hinsichtlich der Beteiligung an solchen Gefäßverschlüssen untersucht [2,12]. Sollten sich weitere Hinweise auf die Expression von Adhäsionsmolekülen auf leukämischen Blasten und deren Beteiligung an leukostatischen Prozessen ergeben, sind potentielle Therapieverfahren mit spezifischen Hemmstoffen, die Signalkaskaden und direkte Interaktionen mit dem Gefäßendothel blockieren, denkbar, jedoch derzeit noch spekulativ [2].…”
unclassified